Ultra wireless transmission waveform measurement with IEEE802.15.3a - Promwong, Sathaporn; Rankhamrat, Borromwut; Thavonsassanavong, Thanin; Chaiyapong, Saksit (My University, 2013)
Ultra wireless transmission waveform with IEEE802.15.3a or ultra wideband (UWB) band is expected to applied to wireless personal area networks (WPANs) such as the ranging in the home network and the office and broadband multimedia systems. Ultra wideband impulse radio (UWB-IR) transmission waveform is investigated by using extended Friis' transmission formula baseded on measurement data. This paper, we conderation the performance system design on ultra wireless system for WiMedia area networks. The received signal and isotropic template receivers are considered based on Friis transmission formula. In this experimental study, the biconical antennas are uesd as the transmitter (Tx) and the receiver (Rx) antennas. The rectangular passband, which is satisfied the full band of UWB spectrum definition and Federal Communications Commission (FCC) indoor and outdoor limit spectral masks, is used as the transmitted UWB signal. The channels are measured in an indoor environment by using a vector network analyzer (VNA). The UWB transmission gains of received signal and isotropic template receivers are shown and compared in results. © 2013 IEEE.
Keywords: Friis' transmission formula; impulse radio; ultra wireless; UWB-IR; waveform distortion